Macromol. Theory Simul. 1/2018. Issue 1 (24th January 2018) - Fitzgerald, Barry W.; Briels, Wim J.
Abstract : Front Cover : An updated mesoscopic model based on the response of a vectorial structure parameter for transient forces between interacting star polymers is presented. Two independent processes, mixing and deformation, contribute to the relaxation of structure of two interpene trating star polymers. The model reproduces flow direction forces from simulations. More information can be found in article number1700069 by Barry W. Fitzgerald and Wim J. Briels.